PENGAKUAN DAN PERLINDUNGAN HAK ATAS TANAH MASYARAKAT ADAT DALAM HUBUNGANNYA DENGAN USAHA PERTAMBANGAN - Zakaria Abbas; Evi Oktarina (Fakultas Hukum Universitas IBA Palembang, 2020)
ABSTRACT Mining business activities in the area of ​​indigenous peoples in recent decades have caused quite a number of problems which are considered to be detrimental to their interests, only in terms of the recognition and protection of indigenous and tribal peoples so far they have not been recognized and protected optimally in implementing communal management rights, both land rights , territories, cultures and natural resources obtained from generation to generation as well as those obtained through other mechanisms that are valid according to local customary law. Not yet optimal recognition and role of indigenous and tribal peoples in mining business activities will lead to conflicts in the mining business activities In the Oil and Gas Law, Law No. 4 of 2009 concerning Mineral and Coal Mining (UU Minerba) does not provide specific provisions regarding indigenous peoples, in the Minerba Act the regulation is more general in nature regarding the role and involvement of the community than a more specific category of indigenous peoples. Protection of indigenous peoples in mining business activities are only contained in Article 11, Article 33 and Article 34 of Law no. 22 of 2001 concerning Oil and Gas